Demographic Features of Turkish Literature Audiences and Applied Analysis of the Factors Affecting Their Reading Preferences, - Poyraz, Y., Korkmaz, M., Yücel, A. S., Aras, G., Çelebi, N., (My University, 2014)
The purpose of this study is to determine factors affecting reading preferences in parallel with the demographic features of Turkish literature audiences. The study lasted approximately for 7 months. (N=650) individuals attended the study in total. The universe of the study is Turkey while the sample of the study is composed of 8 different provinces. These provinces are İstanbul, Ankara, İzmir, Bursa, Kocaeli, Sakarya, Trabzon and Gaziantep. A questionnaire form whose reliability and validity had been ensured before and which was composed of 5 point Likert scale was used in the study. The questionnaire form was reformed in accordance with the topic of the study, it was subjected to validity and reliability test and it was carried into main practice through taking views of experts. Data acquired from the results of main practice was analyzed by using SPSS 18.0 packet program and the value of 0.924 was acquired as Cronbach’s Alpha co-efficient. This value indicates that the measuring tool used in this study is quite reliable. The questionnaire is composed of two sections. In the first section, there are questions with regard to determine demographic features of the participants while in the second section, there are scaled questions composed of 120 items. 0.05 of significance level was taken into account among variables in terms of relations and differences. Methods such as different statistics anova, factor and hypothesis tests were applied in the analysis. Moreover, 4 different literary works were mentioned in the study so as to determine attitudes and behaviors of the participants towards literary works. Opinions of the participants were demanded about novels such as İntibah (Rebirth), Araba Sevdası (Ambition for Car), Mai ve Siyah (Blue and Black) and Çalıkuşu (The Wren). At the end of the study, it was found out that the participants followed academic publications more frequently, the use of computer and internet had an effect on reading e-book and up-to-date books were read more than those books written in a foreign or ancient language (Ottoman Turkish). Furthermore, it was determined that education and age variables of the participants had an effect on reading habits while gender, age and education variables had an effect in some reading factors.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Literature; Education; Audience; Reading; Effect; Factor; Turkish; Demographic